Exploring the Impact of Urinary Metal Exposure on Blood Lipid Profiles in Chinese Adults: Mediating Roles of Health‐Related Indicators - Jianqin Zhong; Zixuan Xu; Tingting Yang; Leilei Liu; Renhua Zhang; Yuan Wang; Linfei Huang; Feng Hong (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The relationship between urinary metal exposure and lipid profiles remains unclear, particularly regarding potential mediators. This study aimed to investigate associations between urinary metals and lipid levels and to explore mediating health indicators. Methods We included 14 817 participants in the CMEC (Chinese Multi‐Ethnic Cohort) study baseline data. Twenty‐one urinary metals, 16 health indicators, and lipid profiles were measured to explore their relationships. Results In single‐metal models, each unit increase in urinary zinc was associated with higher total cholesterol by 12%, triglycerides by 29%, and low‐density lipoprotein cholesterol by 14%, along with lower high‐density lipoprotein cholesterol by 3%, and increased odds of dyslipidemia (odds ratio, 1.76 [95% CI, 1.55–2.01]). In contrast, higher urinary sodium was associated with lower total cholesterol (−12%), triglycerides (−6%), low‐density lipoprotein cholesterol (−7%), and decreased dyslipidemia risk (odds ratio, 0.87 [95% CI, 0.83–0.92]). In mixed exposure models, zinc, manganese, and cobalt were major contributors to dyslipidemia. Quantile regression revealed stronger effects of zinc in individuals with higher lipid levels. Mediation analysis showed that waist‐to‐hip ratio and uric acid mediated 27.2% and 12.0% of the metal–dyslipidemia relationship, respectively. Conclusions Urinary metal exposure is significantly associated with lipid abnormalities, particularly among individuals with higher lipid levels. Specific metals may influence lipid metabolism via adiposity and uric acid pathways. Therefore, reducing exposure to certain urinary metals may contribute to dyslipidemia prevention and cardiovascular risk reduction.